Digital Design Essentials(Photocopy) - Richard S. Sandige (American : Prentice Hall, 2002)
This book present logic and switching circuits and digital system design from a hardware and software standpoint. The emphasis is on hardware. The text was designed as a first course in digital design for freshmen or sophemores studying Computer Engineering, Computer science and electrical Engineering. However, the format and abundant example also make the text ideal for self study. Someone with a background in another filed might use the book to improve his or her ability to build digital hardware circuits. The only prerequisite is computer literacy.
There are book including three part and seven chapter
Part I: Combinational Logic Design
Chapter 1: Number systems, Number Representations and Codes
Chapter 2: Boolean Algebra, functions and Minimization
Chapter 3: Analyzing and Synthesizing Combinational Logic Circuits
Chapter 4: Additional Circuit Synthesis Techniques.
Part II: Sequential Logic Design
Chapter 5: Feedback Circuits
Chapter 6: Introduction to Sequential Circuits Design
Part III: HDL Chip Design
Chapter 7: VHDL Synthesis by Example.
Keywords: Digital Electronics; Digital Design Essentials